Government Policy Effects and Sustainable Entrepreneurship: Implications for Nigeria’s Economic Growth - Ibrahim Musa (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study examines the effects of government policies on sustainable entrepreneurship and their implications for economic growth in Nigeria. Recognising the strategic importance of sustainability-oriented enterprises in promoting long-term economic resilience, the study assesses how regulatory frameworks, fiscal incentives, institutional quality, and public investment shape entrepreneurial behaviour and business sustainability outcomes. Using annual time-series data from 1986 to 2022 and applying econometric techniques such as Ordinary Least Squares (OLS), Autoregressive Distributed Lag (ARDL) analysis, and diagnostic tests, the research empirically evaluates the relationships among government policy variables, sustainable entrepreneurship indicators, and economic performance, measured by GDP growth. Findings reveal that supportive government policies, particularly tax incentives, regulatory reforms, and public investment in sustainable sectors, significantly enhance sustainable entrepreneurial activities and contribute positively to economic growth. Conversely, excessive regulatory burdens hinder entrepreneurship and slow economic expansion. Descriptive statistics further highlight uneven regional development across renewable energy investment, infrastructure, and human capital, which collectively influence entrepreneurial outcomes. The study underscores the critical role of coherent, well-implemented policies in promoting sustainable entrepreneurship as a pathway for economic diversification, innovation, and long-term growth in Nigeria. It concludes with policy recommendations to strengthen institutional capacity, improve regulatory efficiency, and expand sustainability-focused incentives.